A lovely lie - Hendricks, Jaime Lynn (Scarlet, an imprint of Penzler Publishers, 2024)
Is it better to believe a lovely lie or to know the horrible truth? 1999: The night of their senior picnic, Scarlett Russo and her best friend Pepper were involved in a car accident that left two of their classmates dead. Afterward, they lied to the police, protecting each other from the consequences. Then Pepper left town and Scarlett never heard from her again... Now: Twenty-two years later, Scarlett has buried that deadly incident deep in her mind and built a comfortable life for herself, working in a hotel on the west coast of Florida and raising her teenage son with her husband Vince. Her peace is disrupted, however, when Pepper's daughter shows up with news of Pepper's death. Zoey is twenty-one and studying to be an investigative journalist. She has a cryptic letter from Pepper addressed to Scarlett that alludes to the events of that fateful night and Pepper's initial intentions to get an abortion. Now Zoey wants answers about her mother's past. Who is Zoey's father? And what really happened after the senior picnic? As Zoey continues to dig into the past, all of Scarlett's buried secrets threaten to rise to the surface. Jaime Lynn Hendricks, "the queen of the page-turner" (Ashley Winstead), will have you questioning who you can trust in this intricately twisted thriller.